Application of geographical information system (GIS) in analysis and detection of microbial contamination in water supply network - Masoud Yousefi; Fatemeh Mesbahi; Iraj Abbasi; Mahboobeh Kousha; Kourosh Rahmani (Shiraz University of Medical Sciences, 2020)
Background: Nowadays, in the world's optimal management of science and technology, the use of geographical information system (GIS) is a necessity. In this study, GIS was used to analyze and detect microbial contamination in the water supply system of Masiri city. Methods:A cross-sectional study utilizing spatial analysis techniques was conducted to find out the water quality problems of water supply system.  In this descriptive-analytical study, 400 water samples from all groundwater resources of Masiri city were conducted during two periods of dry and wet season. Residual chlorine, MPN and E.coli of the samples were determinate. Results: Results were compared with national standards and analyzed using SPSS and ArcView software. Concentration distribution map in GIS and the factors affecting Residual chlorine, MPN and E.coli changes were investigated.  According to the results obtained in ArcView, it is necessary to improve the microbial quality of Masiri water distribution network in some places, which can be improved by proper management of chlorination and defects. Conclusion:It is concluded that a combination of water quality parameters and GIS methods is very useful asGIS provides efficient capacity to visualize the spatial data.